Genetic structure and knockdown resistance (kdr) mutations in Aedes albopictus (Skuse) (Diptera: Culicidae): Implications for dengue fever transmission in southeastern China. - Shi-Yuan Lin; Pei-Ling Ye; Ya-Hui Chen; Nan Zheng; Cheng Wu; Li-Hua Xie (PLoS ONE)
Dengue fever, transmitted by Aedes albopictus in China, is a major public health issue. The emergence of kdr gene mutations in Ae. albopictus has reduced the efficacy of insecticide-based control. We investigated the genetic structure of eight Ae. albopictus populations from China's southeastern coastal region, analyzing genetic diversity, population structure, and the prevalence of kdr mutations in relation to dengue fever incidence. Allelic diversity was moderate, with the number of alleles ranging from 2 to 6 and effective number of alleles from 1.52 to 5.00. Genetic clustering revealed four groups with 0.71% to 1.81% variation, indicating moderate differentiation. The coefficient of genetic differentiation value was 0.07 to 0.18, and Nm values 1.13 to 3.25. Except for Foshan and Sanming, four populations showed deltamethrin resistance, 4.31 to 18.87-fold. The voltage-gated sodium channel (VGSC) gene analysis identified non-synonymous mutations, with I1532 mutations absent in Sanming and F1534 present in all. Four populations showed resistance to deltamethrin, with resistance levels varying significantly. The VGSC gene analysis revealed multiple non-synonymous mutations associated with resistance, particularly at positions I1532 and F1534. No significant correlation was found between dengue fever incidence, kdr mutations, and genetic indicators, indicating a consistent potential for disease transmission. However, populations with higher genetic diversity had lower frequencies of F1534 and higher frequencies of I1532I mutations. The findings underscore the significant influence of kdr mutations on the effectiveness of mosquito control strategies. The presence of these mutations necessitates the implementation of alternative insecticides and integrated pest management approaches to sustainably reduce Ae. albopictus populations and mitigate the spread of dengue fever.